The Iraqi economy between the planning method and the liberalism and its reflection on the investment by human capital, analysis research during the period 1990-2016 - احمد داود عبد الجبار; فتاح عبد الجبار محمود (Journal of Economics and Administrative Sciences, 2017)
Abstract: The use of economic resources enjoyed Iraq by especially oil resources, which constitute the main source of financial revenue, would the economic surplus outside the oil sector increases by mobilizing and rallying the labor power and turn it into an access capitalism, , was the cause of "the inaction of the productive sectors of the economy, made the investment planning process and even investment in human capital was not rationality with the increasing number of unemployed, particularly certificates and specializations high campaign, direction of the government towards market liberalism after 2003 through the, was focused not follow a clear economic policies, and the absence of planning, and the absence of rational allocation of economic resources, led to a waste by human capital and investment in Market liberalism